Report of the Survey of Small Scale and Cottage Industries in Baroda District - Planning Commission (Planning Commission, 1957)
It gives me great pleasure to submit this report to the Research Programmes Committee of the Planning Commission The scheme of research was prepared in the year 1957-58 and submitted to the Research Programmes Committee for approval. When it was actually prepared there was the impression going round that the two industries viz. Calico printing in Padra and lacquer wood work in Sankheda each employed a large number of families and that we may have to resort to the random sample, method in selecting our units of study.
Planning Commission, Research Programme Committee